Parent-Mediated Reading Interventions With Children Up To Four Years Old: A Systematic Review. (March 2015) - Sloat, Elizabeth A.; Letourneau, Nicole L.; Joschko, Justin R.; Schryer, Erin A.; Colpitts, Jennifer E.
<x xml:space="preserve">Abstract</x> Research demonstrates that literacy and academic achievement are predicated on the emergent literacy knowledge and skills children acquire from birth up to 4 years of age. Parents are children's first and most important language and literacy teachers, yet not all parents have the capacity to establish an adequate early literacy foundation. Efforts to address this situation have resulted in numerous programs aimed at fostering emergent literacy development. This systematic review evaluates evidence on the effectiveness of parent-mediated interventions that increase the time parents spend reading with young children up to 4 years old. Four studies met inclusion criteria, reporting outcomes for 664 children. Three provided data for meta-analysis of effects on reading duration. The standardized mean difference in reading duration was 1.61 (95% CI, 1.03, 2.19 fixed-effect), favoring intervention over control. Results indicate that interventions aimed at increasing the amount of time parents spend reading interactively with their children yield positive results. Findings also demonstrate that pediatric primary care providers are well positioned to deliver reading promotion programs to parents and preschoolers.